Women's Leadership and Digital Capabilities: The Impact on MSME Performance through Job Satisfaction - Albert, Albert; Hutabarat, Chintya Yohana Putri; Chandra, Felixco; Nesia, Yesha; Hairinsyah, Kesuma; Pasaribu, Ester YYN (Utan Kayu Publishing, 2025)
Women-owned MSMEs (MSMEs) play a significant role in the local economy, but still face challenges in improving business performance, particularly related to leadership, digital capabilities, and psychological well-being at work. This study aims to analyze the influence of women's leadership and digital capabilities on MSME performance, with job satisfaction as an intervening variable. This study used a quantitative approach through a survey of 120 women-owned MSMEs in Medan City. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that women's leadership and digital capabilities have a positive and significant effect on job satisfaction. Digital capabilities also have a positive and significant direct effect on MSME performance, while women's leadership does not show a significant direct effect on MSME performance. Furthermore, the results of the indirect effect test indicate that job satisfaction plays a significant role in mediating the relationship between women's leadership and MSME performance, as well as between digital capabilities and MSME performance. These findings emphasize the importance of job satisfaction as a psychological mechanism in explaining the influence of leadership and digital capabilities on the performance of women-owned MSMEs. This study has implications for leadership development, digital capability enhancement, and the formulation of sustainable policies for empowering women-owned MSMEs.